Pengaruh Implementasi Pengendalian Intern, Pemanfaatan Teknologi Informasi, dan Total Qualitymanagement Terhadap Penerapan Good Governance Di Lembaga Amil Zakat - Fatmaningrum, Erni Suryandari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The purpose of the research is to know the effect of intern controlling implementation, the utilize of information technology and total quality management on good governance application on amil zakat institution. The participants on this research are the employee of amil zakat institution which is located in Yogyakarta. The technique of data collecting is by spreading the questioners. The amount of questioners is 100 questioner. This research uses Partial Least Square (PLS) as the analysis tool because the data that can be processed are only 42 questioners. Based on analysis which had been done by the researcher, it can be concluded that intern controlling implementation., the utilize of information technology, and total quality management give the positive and significant effect on good governance application with the value of 51,6 % and the rest of it is from the variable outside of this research. The most effect variable on good governance apllication is the utilize of information technology.